Exopolysaccharide production by seven basidiomycetous fungi and their antioxidant and immunomodulatory activities against Salmonella infection - Thanawut Chotmanee; Thanawut Chotmanee; Nakarin Suwannarach; Nakarin Suwannarach; Nakarin Suwannarach; Jaturong Kumla; Jaturong Kumla; Jaturong Kumla; Rewat Phongphisutthinant; Rewat Phongphisutthinant; Supakit Chaipoot; Supakit Chaipoot; et al. (Frontiers in Cellular and Infection Microbiology)
The discovering new fungal strains, optimal production, and understanding the fundamental aspects of exopolysaccharides (EPs) are important to utilize them in an industrial, medical, and biotechnological perspective. In this study, the optimal conditions for EP production from seven basidiomycetous fungal strains were investigated. The results indicated that six fungal species, Schizophyllum commune, Ganoderma fornicatum, G. williamsianum, Earliella scabrosa, Favolus tenuiculus, and Pycnoporus sanguineus, produced the highest EP yield in potato dextrose broth. The highest yield of EPs produced by Lentinus sajor-caju was obtained in mushroom complete medium broth. It was found that a pH value between 6 and 8 in the liquid culture media promoted EP production. The highest EP yield was obtained for 10 to 14 days which depends on fungal strain. Interestingly, this present study revealed the first report of EP production from G. fornicatum, G. williamsianum, E. scabrosa, F. tenuiculus, and P. sanguineus, including the genera Earliella and Favolus. The obtained crude EPs showed water solubilization ability. The Fourier-transform infrared spectroscopy spectra exhibited typical carbohydrate patterns in all crude EPs. Monosaccharide composition analysis revealed that the crude EPs were primarily composed of glucose, followed by fructose, allose, and allulose, with variations depending on the fungal strain. Additionally, crude EPs demonstrated positive antioxidant potential. Finally, we determined the anti-Salmonella and immunomodulatory effects of crude EPs from S. commune, G. fornicatum, and L. sajor-caju due to their high EP yield. Pretreatment of mouse macrophages with these fungal EPs enhanced the phagocytic killing activity of Salmonella-infected macrophages. Upregulations of pro-inflammatory cytokine expression in macrophages were detected in the fungal EPs-treated groups. Our study reported the optimizing conditions for EP production from several strains of Basidiomycetous fungi and their potential as an alternative to antibiotics for multidrug-resistant Salmonella infection.